2013
DOI: 10.1002/art.38137
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association Study of Dermatomyositis Reveals Genetic Overlap With Other Autoimmune Disorders

Abstract: Objective To identify new genetic associations with juvenile and adult dermatomyositis (DM). Methods We performed a genome-wide association study (GWAS) of adult and juvenile DM patients of European ancestry (n = 1178) and controls (n = 4724). To assess genetic overlap with other autoimmune disorders, we examined whether 141 single nucleotide polymorphisms (SNPs) outside the major histocompatibility complex (MHC) locus, and previously associated with autoimmune diseases, predispose to DM. Results Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 39 publications
5
111
0
1
Order By: Relevance
“…This is also true for genetic studies. In fact, the first genome-wide association study in patients with inflammatory myopathy [78] was completed thanks to a genetic biorepository shared by different centers and countries. This project will certainly enhance our understanding of the pathogenesis of myositis and will probably help to define new diagnostic and therapeutic approaches for these patients.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…This is also true for genetic studies. In fact, the first genome-wide association study in patients with inflammatory myopathy [78] was completed thanks to a genetic biorepository shared by different centers and countries. This project will certainly enhance our understanding of the pathogenesis of myositis and will probably help to define new diagnostic and therapeutic approaches for these patients.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…They are among human homologue candidates of DAF-12/vitamin D receptor (VDR) target genes [2,7,8,12]. However, Miller et al reporting on GWAS of Dermatomyositis (DM), found a genetic overlap with other ADs, as the first genetic predispositions towards ADs shared with DM [13]. The latest case is rpc-1 responsible for both the scleroderma and cancer [14].…”
Section: One Of Our Recent Experiences Is As Followmentioning
confidence: 99%
“…The latest case is rpc-1 responsible for both the scleroderma and cancer [14]. Moreover, other patterns of genetic overlap across ADs have emerged [13,15]. Likely, a malfunction of VDR could affect the pathogenesis of RA and associated cancers expanding to many other ADs, Paraneoplastic Neurological Diseases(PND) and DM (Table 1) [1,13,14,16,[17][18][19][20][21][22][23][24].…”
Section: One Of Our Recent Experiences Is As Followmentioning
confidence: 99%
“…A Myositis Genetics Consortium dermatomyositis (DM) GWAS also suggests genetic overlap with other autoimmune disorders. 1 We sought to extend these findings to identify novel genetic risk factors in a large cohort of adult/juvenile patients with DM and polymyositis (PM), by genotyping immune-related single nucleotide polymorphisms (SNPs) not captured through the DM GWAS. 1 …”
mentioning
confidence: 99%
“…2 Unique SNPs were identified (n=233), of which 99 had not been directly genotyped or captured (r 2 ≥0.8 with genotyped SNPs) through our DM GWAS. 1 These 99 SNPs were genotyped using Sequenom in 1001 European Caucasian individuals with definite/probable adult or juvenile DM or PM. 34 Eighty-three SNPs passed quality control.…”
mentioning
confidence: 99%